The additive manufacture processing and machinability of CrMnFeCoNi high entropy alloy. (15th January 2021) - Litwa, Przemyslaw; Hernandez-Nava, Everth; Guan, Dikai; Goodall, Russell; Wika, Krystian K.
Abstract: We report a study of the machining characteristics of a High Entropy Alloy, CrMnFeCoNi (Cantor's Alloy). The alloy in powder form is first used to Additively Manufacture a relatively large block by Selective Laser Melting. This block provides the material for a parametric study of the machining response in comparison to a reference AISI 304L stainless steel, both in terms of the surface finish obtained for different machining parameters, and the tool wear. It was found that the CrMnFeCoNi alloy has in fact better machinability than the AISI 304L stainless steel, and indications from the machined surface are that this is due to the plastic behaviour in this alloy, with good, but not excessive, strength, and significant ductility. While this behaviour may not be replicated in all HEAs, it shows that alloys with good machinability can be found in this class, and that early assessment of machinability can help guide alloy design activities. Graphical abstract: Unlabelled Image Highlights: CrMnFeCoNi has been processed by SLM following a design of experiments (DoE) achieving high density. No local segregation was found in as-built material keeping the homogeneity of the high entropy composition. CrMnFeCoNi has been successfully machined following a parametric approach achieving minimum surface roughness and defects. The machinability design space and tool wear have been fully characterised.